2005
DOI: 10.1007/s10350-004-0853-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Mesocolic and Pelvic Diverticular Abscesses of the Left Colon: A Prospective Study of 73 Cases

Abstract: Considering the poor outcome of pelvic abscess associated with acute left-sided colonic diverticulitis, percutaneous drainage followed by secondary colectomy seems justified. Mesocolic abscess by itself is not an absolute indication for colectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
108
1
15

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(127 citation statements)
references
References 22 publications
(23 reference statements)
3
108
1
15
Order By: Relevance
“…However, Ambrosetti et al 6,16 observed that both intraabdominal and pelvic abscesses were associated with a significant risk of surgery compared with a mesocolic abscess. The latter had a lower risk of requiring surgery once adequately drained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Ambrosetti et al 6,16 observed that both intraabdominal and pelvic abscesses were associated with a significant risk of surgery compared with a mesocolic abscess. The latter had a lower risk of requiring surgery once adequately drained.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Studies have shown that the incidence of an abscess complicating an episode of diverticulitis ranges from 17-19%. [4][5][6] The American Society of Colon and Rectal Surgeons recommended that small mesocolic abscesses can be treated with intravenous antibiotics. 7,8 In contrast, large abscesses may be drained percutaneously or by an open procedure.…”
mentioning
confidence: 99%
“…In addition, well-localized fluid collections of appropriate density and consistency (i.e., lack of extensive loculations) may be drained percutaneously with acceptable morbidity and mortality [74][75][76][77][78].…”
Section: Statementmentioning
confidence: 99%
“…A study of the long-term outcomes of diverticular abscesses reported that 15 % of patients with a mesocolic abscess required surgery during their first admission compared with 39 % of patients with pelvic abscesses [21]. After a median follow-up period of 43 months, 42 % of patients managed non-operatively for their mesocolic abscess went on to require surgical intervention compared with 53 % of those with a pelvic abscess.…”
Section: Management Of Diverticular Abscessesmentioning
confidence: 99%